2021
DOI: 10.1111/echo.15249
|View full text |Cite
|
Sign up to set email alerts
|

A study of 399 cardiac tumors: Characteristics of echocardiography and pathological features

Abstract: Aims: This study aimed to summarize the transthoracic echocardiography (TTE) characteristics of cardiac tumors with different pathologies. Methods:The data of 399 patients with cardiac tumors confirmed by pathology, who had undergone surgical resection were consecutively collected in our hospital between January 1, 2011 and December 31, 2019. The TTE characteristics were summarized and compared with the pathology.Results: Mean patient age was 49.8±15.7 years (22 children and 377 adults), and 62.2% were female.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…Pathological immunohistochemical results showed that the emboli stained positive for vimentin, calretinin, CD31 and CD34 but were negative for CD68, CK, CK5/6 and F8. In addition, AB and PAS were positive, and the above results are consistent with the pathological characteristics of CM[ 5 - 7 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Pathological immunohistochemical results showed that the emboli stained positive for vimentin, calretinin, CD31 and CD34 but were negative for CD68, CK, CK5/6 and F8. In addition, AB and PAS were positive, and the above results are consistent with the pathological characteristics of CM[ 5 - 7 ].…”
Section: Discussionsupporting
confidence: 75%
“…Alcian blue staining (AB) and periodic acid Schiff staining (PAS) were also positive (Figure 4 ). The above pathological findings were consistent with the pathological features of myxoma[ 5 - 7 ]. Combined with the results of preoperative echocardiography and postoperative pathological examination, it can be inferred that the acute lower extremity arterial embolism was caused by shedding of a left CM.…”
Section: Case Presentationsupporting
confidence: 85%
“…Primary cardiac tumors are very rare, with a reported incidence on autopsy of .002%–.3% and a prevalence of .001%–.03% 4,5 . The incidence of cardiac teratomas is extremely low: pericardial teratomas are the most common type, while intracardiac teratomas are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cardiac tumors are very rare, with a reported incidence on autopsy of .002%-.3% and a prevalence of .001%-.03%. 4,5 The inci- Although the mass was located in the right ventricular outflow tract, due to its small size, it did not affect the patient's cardiac hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of medical imaging technology and the enhancement of people's health awareness, increasingly atrial tumors have been discovered and finally diagnosed ( 13 ). Echocardiography is a primary tool for the assessment of atrial tumor, providing an accurate assessment of tumor size, location, and attachment site and should assist in surgical planning ( 14 , 15 ). Compared with benign atrial tumors, the specific characteristics of malignant atrial tumors on echocardiography are still unclear.…”
Section: Discussionmentioning
confidence: 99%